2016
DOI: 10.1259/dmfr.20150400
|View full text |Cite
|
Sign up to set email alerts
|

Dental panoramic indices and fractal dimension measurements in osteogenesis imperfecta children under pamidronate treatment

Abstract: Children with OI presented cortical bone alterations after PAM treatment. Both MCW and the FD of the cortical bone were higher in children with OI after PAM treatment. It is argued that cortical bone should be considered for analyzing patients with OI, as well as to monitor the progress of PAM treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 39 publications
1
69
1
3
Order By: Relevance
“…Several recent studies reported that the findings of cortical bone are more reliable than those of the trabecular bone for the diagnosis of osteoporosis [13, 28, 29]. For osteoporosis in Brazilian male and female subjects, MCW and FD analyses of mandibular cortical bone were found to be more reliable than that of anterior and inferior regions of the trabecular bone [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies reported that the findings of cortical bone are more reliable than those of the trabecular bone for the diagnosis of osteoporosis [13, 28, 29]. For osteoporosis in Brazilian male and female subjects, MCW and FD analyses of mandibular cortical bone were found to be more reliable than that of anterior and inferior regions of the trabecular bone [13].…”
Section: Discussionmentioning
confidence: 99%
“…FDs of the trabecular bone are widely used to identify the complexity and structure of the bone. It is calculated at various anatomical sites using different imaging modalities to observe the changes in bone pattern [29]. Watanabe at al reported that the FD of male group showed a higher degree of trabecular bone architecture and indicated that the structure of their bone is less prone to osteoporotic fractures [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much has been studied about bone quality of dental structures of individuals with systemic conditions that may result in decreased BMD, such as osteoporosis (4), postmenopause (10), celiac disease (11) and osteogenesis imperfect (12). However, there are no studies with radiomorphometric analysis in individuals with T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…Procurando verificar a relação dos índices radiomorfométricos em radiografias panorâmicas de crianças com diferentes tipos de osteogênese imperfeita, em tratamento com pamidronato intravenoso, conclui-se que, para este grupo de risco, as crianças apresentam corticais mandibulares mais finas e porosas no início do tratamento, e que a melhoria da qualidade do osso cortical pós-tratamento pode ocorrer conforme o tipo de osteogênese imperfeita e número de ciclos de pamidronato. A análise da densidade óssea torna-se de extrema importância para a avaliação do progresso da utilização de pamidronato intravenoso 15 . Novos estudos são necessários para verificar se esses índices podem também predizer o risco de fraturas por osteoporose e elucidar se, em homens idosos, os índices radiomorfométricos possuem a mesma aplicabilidade que a observada em mulheres na pós-menopausa 7 .…”
Section: Discussionunclassified